INTERVAL ANALYSIS AND ITS APPLICATION THE DESIGN OF THE SERVER COMPUTER SYSTEMS - Anoprienko, A.Y.; Ivanitsa, S.V.; Hamza, Al Rababa (Radio Electronics, Computer Science, Control, 2013)
Emergence the uncertainties and ambiguities in the implementation of complex data in calculations of parameters server computer systems is a factor that justifies the use of methods and means of interval analysis in developing improved methods of key parameters server-based computing systems and networks, enabling more efficient use of server computer resources. The article describes basic properties of intervals and operations on them to demonstrate the advantages of using interval data types as input and output parameters; shows the transition from the traditional view of network parameters to interval; gives a demonstration of the use of computational methods for interval calculation example response time queries.